Study on the influence of TiO2 nanoparticles on the breakdown voltage of transformer oil under severe cold conditions. - Chunxu Qin; Wenjie Lin; Yongxiang Huang; Liqiang Liu; Huichun Hua; Huijuan Liang (PLoS ONE)
The modified nanoparticles can significantly improve the insulation characteristics of transformer oil. Currently, there is a lack of research on the actual motion state of particles in nanofluid to further understand the micro-mechanism of nanoparticles improving the insulation characteristics of transformer oil. In this study, the nanofluid containing 0.01g/L of TiO2 with a particle size of 20nm is prepared using the thermal oscillation method. Breakdown voltage tests are carried out. The experimental test results show that adding nanoparticles can significantly reduce the breakdown probability of transformer oil. The more the water content, the less the enhancement effect of the nanofluid on breakdown voltage. The higher the temperature, the stronger the enhancement effect of the nanofluid on breakdown voltage. Finally, the polarization process of nanoparticles and the trajectory of charged particles in the transformer oil under different electric fields are simulated using COMSOL to further analyze the influence mechanism of nanoparticles on the insulation characteristics of transformer oil. The simulation results show that under the action of the electric field, nanoparticles polarize and generate charge shallow traps to adsorb electrons, reducing the high-speed free charges in the oil, and indirectly increasing the breakdown voltage.